Beyond rehabilitation in MS: Insights from non-invasive brain stimulation. (September 2019) - Leocani, Letizia; Chieffo, Raffaella; Gentile, Antonietta; Centonze, Diego
Although the number of disease-modifying treatments for people with multiple sclerosis (pwMS) has meaningfully increased in the past years, targeting repair or compensation for central nervous system damage associated with the disease process remains an important clinical goal. With this aim, neurorehabilitation is a powerful approach targeting central nervous system plasticity. Another driver of brain plasticity is non-invasive brain stimulation (NIBS), receiving recent attention in neurology, particularly for its potential synergy with neurorehabilitation and as add-on treatment for several neurological conditions, from pain to fatigue to sensorimotor and cognitive deficits. In this review, we will resume the evidence exploring the neurobiological basis of NIBS and its applications to MS-related conditions.